(untitled) (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2026)
This study aimed to examine the effect of different concentrations of duck manure on the growth of Azolla pinnata and to determine the optimal concentration that promotes the best growth performance without reducing the quality of the cultivation medium. The experiment consisted of five treatments: A1 (without duck manure), A2 (20% duck manure + 80% soil), A3 (30% duck manure + 70% soil), A4 (40% duck manure + 60% soil), and A5 (50% duck manure + 50% soil), with an initial Azolla pinnata density of 200 g/m². The results showed that the application of duck manure had a highly significant effect on the growth rate of Azolla pinnata (P<0.01). Among the treatments, A3 produced the highest biomass increase, indicating the most favorable growth response. Duck manure contains essential nutrients such as nitrogen (3.40–4.42%), phosphorus (15.54–17.20%), and potassium (8.50–8.63%), which play vital roles in photosynthesis and tissue formation. These nutrients accelerate cell division and chlorophyll production, thereby enhancing the growth rate of Azolla pinnata. Compared with other organic fertilizers such as chicken, cow, or compost manure, duck manure provides higher nutrient availability and is more readily absorbed by aquatic plants. Therefore, the combination of 30% duck manure and 70% soil can be considered the optimal composition for Azolla pinnata cultivation and has strong potential to be developed as an environmentally friendly organic fertilizer within sustainable agricultural systems.